The Influence of the Argument-Driven Inquiry Learning Model in Physics Learning with the STEAM Approach on the Scientific Argumentation Ability - Epriliyani, Ekaningtyas Wahyu; Deta, Utama Alan (Universitas Negeri Surabaya, 2025)
Argument-driven Inquiry (ADI) is a laboratory-based learning model in which students can be involved in argumentation activities to increase understanding and practice argumentation skills. This research aims to analyze the influence of Argument-Driven Inquiry in physics learning using the STEAM approach on students' scientific argumentation abilities. This research design uses a pretest and posttest control group design. This research used two class groups: the experimental and control classes. Data obtained through pretest and posttest were tested using SPSS. This research shows that argument-driven inquiry in physics learning with the STEAM approach influences students' scientific argumentation abilities. After implementing the learning, scientific argumentation skills are at level 2. Keywords: Argument-Driven Inquiry, Scientific Argumentation, STEAM Approach